Rare Earth Element (REE)-Dependent Growth of Pseudomonas putida KT2440 Relies on the ABC-Transporter PedA1A2BC and Is Influenced by Iron Availability - Wehrmann, Matthias; Berthelot, Charlotte; Billard, Patrick; Klebensberger, Janosch (Frontiers in Microbiology, 2019)
In the soil-dwelling organism Pseudomonas putida KT2440, the rare earth element (REE)-utilizing and pyrroloquinoline quinone (PQQ)-dependent ethanol dehydrogenase PedH is part of a periplasmic oxidation system that is vital for growth on various alcoholic volatiles. Expression Production of PedH and its Ca2+-dependent counterpart PedE is inversely regulated in response to lanthanide (Ln3+) bioavailability, a mechanism termed the REE-switch. In the present study, we demonstrate that copper, zinc, and in particular, iron availability influences this regulation in a pyoverdine-independent manner by increasing the minimal Ln3+ concentration required for the REE-switch to occur by several orders of magnitude. A combined genetic- and physiological approach reveals that an ABC-type transporter system encoded by the gene cluster pedA1A2BC is essential for efficient growth on 2-phenylethanol with low (nanomolar) Ln3+ concentrations. In the absence of pedA1A2BC, a 100-fold higher La3+-concentration is needed for PedH-dependent growth but not for the ability to repress growth based on PedE activity. From these results, we conclude that cytoplasmic uptake of lanthanides through PedA1A2BC is essential to facilitate REE-dependent growth on 2-phenylethanol under environmental conditions with poor REE bioavailability. Our data further suggest that the La3+/Fe2+/3+ ratio impacts the REE-switch through the mismetallation of putative La3+-binding proteins, such as the sensor histidine kinase PedS2, in the presence of high iron concentrations. As such, this study provides an example for the complexity of bacteria-metal interactions and highlights the importance of medium compositions when studying physiological traits in vitro in particular in regards to REE-dependent phenomena.